UTILIZATION OF CARTONS WASTE CHIPS IN MANUFACTURING OF FIBER COMPOSITE BOARDS - Dilgash Yaseen; Aree Abdulqader (Mesopotamia Journal of Agriculture)
This experiment was implemented to study the physical and mechanical properties of Medium Density Fiberboard (MDF) manufactured from Old Corrugated Containers OCCs using three variables including density of board (0.6 g/cm3 and 0.7 g/cm3), resin content of urea-formaldehyde (8 %, 10 % and 12 %) and pressing time (25, 30 and 35 minutes). Results showed that board density proved to be an important factor affecting MDF manufacturing, board density showed significant effects on both Modulus Of Elasticity (MOE)  and Modulus Of Rapture (MOR), while it had no significant effect on Internal Bonding (IB), higher board density (0.7 g/cm3) surpass low board density (0.6 g/cm3). The percent resin content and press time gave a significant effect on mechanical properties except IB. Also, it was noticed a perfection of boards combined at 12% resin contents and 30 minutes of mechanical properties. The triple intercourse between main effects showed to be significant for MOR, MOE and IB, generally boards made of higher density (0.7 g/cm3) with 12% resin content at pressing time 30 minutes developed better mechanical properties than other boards. According to the physical properties, board density showed a significant effect on Water Absorption (WA), Thickness Swelling (TS) and Linear Expansion (LE) after 2 and 24 hours of submersion in water. The resin content at 12 % and pressing time at 30 minutes showed better mechanical and physical properties.